ORIENTASI TASAWUF JALALUDIN RUMI DALAM KONSEP MAHABBAH ILALLAH - Masitoh, Dewi; Nisa, Khoirotun (Jurnal Ilmiah Pendidikan dan Keislaman, 2024)
A complex emotional experience, encompassing feelings of affection, concern and bonding towards someone or something, is known as the feeling of love. In the context of love of God, this often refers to the spiritual dimension where individuals feel a deep and loving love towards the Supreme Being. Love for God can manifest through worship, devotion, and gratitude. This relationship transcends the boundaries of human relationships, leading to a search for spiritual meaning and purpose in life. In Tasawwuf, there are famous figures such as Jalaluddin Rumi who is known for his concept of mahabbah. The concept of love in Jalaluddin Rumi's teachings is a means to achieve perfection, being a self-cleansing process that guides humans towards God. Rumi sees love as a beauty that encourages awareness, turns negativity into positivity, gives peace to a restless soul, provides guidance for a lost heart, becomes a light in the darkness, and as a sweetener in the midst of a sea of bitterness. Love has the ability to provide calmness, positive expectations, compassion, and provide rest for the heart, mind, and can even increase fitness and vigor. The positive energy given by love always affects humans positively, so this is important to study so that the concept of love is not only limited to fellow humans, love for God is the main thing that leads to love for fellow humans. This study uses content or document analysis methods by collecting written data from various sources. The data collected from various sources are then compiled, put together, and analyzed. In the process of data analysis, data that is relevant to the research topic will be prioritized, while data that does not support the research objectives will be ignored. This journal investigates the orientation of jalaludin rumi's Sufism in the concept of mahabbah illallah, exploring the spiritual dimension of his teachings